2018
DOI: 10.1002/andp.201800139
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced Superconductivity Induced by the Constant Electron–Phonon Coupling on a Square Lattice

Abstract: In the present paper, we analyze the properties of the unbalanced superconducting state on a square lattice with the constant value of the electron-phonon coupling function. We conduct our analysis in the framework of the Eliashberg formalism, explicitly considering k-dependence of the electron and phonon dispersion relations. It is found that the balanced superconducting state does not induce itself in the system due to the high value of the electron effective mass. However, in the unbalanced case the thermod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…It can be easily noticed that the superconducting phase ceases to exist for γ ≥ γ C = 0.42. Let us remember that within the momentum approximation with a constant value of the electron-phonon coupling function (g q ∼ g) we got γ C = 0.94 [1]. A similar value, γ C = 0.93, is obtained from calculations in which the momentum transfer is explicitly taken into account in the electron-phonon coupling function (see Fig.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…It can be easily noticed that the superconducting phase ceases to exist for γ ≥ γ C = 0.42. Let us remember that within the momentum approximation with a constant value of the electron-phonon coupling function (g q ∼ g) we got γ C = 0.94 [1]. A similar value, γ C = 0.93, is obtained from calculations in which the momentum transfer is explicitly taken into account in the electron-phonon coupling function (see Fig.…”
supporting
confidence: 74%
“…The results were obtained for the electron-phonon interaction function explicitly dependent on the momentum transfer between electron states.Physical properties of the phonon-induced superconducting state on a square lattice were determined in the present work within the Eliashberg formalism. The initial results, obtained in the limit of momentum approximation (which neglects the self-consistency with respect to Matsubara frequency), were already presented by us elsewhere [1]. There we showed that the balanced superconducting state on a square lattice cannot arise in the case of the constant value of the electron-phonon coupling function (g q ∼ g).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…We are currently investigating this issue extensively. Preliminary results for the ME formalism can be found in [99,100].…”
Section: Resultsmentioning
confidence: 99%
“…We are currently investigating this issue extensively. Preliminary results for ME formalism can be found in the papers [86,87].…”
Section: Summary and Discussion Of Resultsmentioning
confidence: 99%